PENERAPAN MEDIA TIKTOK DALAM PEMBELAJARAN PEMASARAN DIGITAL UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KETERAMPILAN DIGITAL SISWA KELAS X BISNIS DIGITAL (STUDI DI SMKS NU GRESIK TAHUN AJARAN 2024 / 2025) - James Imanuel Imanuel; Finisica Dwijayati Patrikha (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This study aims to determine the differences in learning motivation and digital skills of class X BD students. The number of students sampled and studied in the experimental class was 30 students and in the control class was 30 students. In this study, the research method used was Quantitative research with a Quasi-Experimental approach. The sample taken was all class X BD students totaling 60 students for two classes. With relatively equal initial conditions. Data collection used questionnaires, interviews, drawing tests, and observations. The results of the study can be seen that the learning motivation of the experimental class has an average of 73.33 and digital skills of 75.00. The Control Class learning motivation has an average of 71.33 and digital skills of 71.17. Statistical analysis was carried out using descriptive analysis and the Independent T-test. This shows that there are differences in learning motivation and digital skills between the experimental class taught using Tiktok media and the control class using PowerPoint.